2009
DOI: 10.1590/s0044-59672009000100022
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da predação de Podocnemis expansa e Podocnemis unifilis (Testudines, Podocnemididae) no rio Javaés, Tocantins

Abstract: Podocnemis expansa e P. unifilis são animais de vida longa, com uma demorada maturação sexual, o que influencia uma baixa taxa de substituição de indivíduos. Suas populações são caracterizadas por uma pequena mortalidade dos animais adultos, mas alta taxa de mortalidade de filhotes e embriões. Sendo a predação natural de ninhos e filhotes um dos fatores mais importantes do baixo sucesso de eclosão dessas espécies. No rio Javaés, os ovos e recém-eclodidos podem ser predados por uma grande diversidade de animais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Like the majority of Testudines, these animals are long‐living, with slow sexual maturation, which affects the low rate of replacement of individuals (Alfinito, 1973; Pritchard, 1979). Their incubation may last from 45 to 90 days (Medem, 1969; Cantarelli, 1997) and natural predation is the most important factor associated with the hatching rates of these species (Valle et al, 1973; Salera‐Junior et al, 2009).…”
mentioning
confidence: 99%
“…Like the majority of Testudines, these animals are long‐living, with slow sexual maturation, which affects the low rate of replacement of individuals (Alfinito, 1973; Pritchard, 1979). Their incubation may last from 45 to 90 days (Medem, 1969; Cantarelli, 1997) and natural predation is the most important factor associated with the hatching rates of these species (Valle et al, 1973; Salera‐Junior et al, 2009).…”
mentioning
confidence: 99%
“…The most common predators of P. expansa eggs and hatchlings are the black-headed vulture (Coragyps atratus), the red-headed vulture (Cathartes aura), the lesser yellowheaded vulture (Cathartes burrovianus), the carcara plancus (Polyborus plancus), the yellow-headed caracara (Mivalgo chimachima), the jabiru stork (Jabiru mycteria), the wood stork (Mycteria americana), the maguari stork (Ciconia maguari) and the great white egret (Casmerodius albus) (Salera Júnior et al, 2009). These authors also found mild predation by the tegu lizard (Tupinambis teguixin), the ring-tailed coati (Nasua nasua), crab-eating fox (Cerdocyon thous), cocoi heron (Ardea cocoi), snowy egret (Egretta thula) and the rufescent tiger-heron (Tigrisoma lineatum).…”
Section: Discussionmentioning
confidence: 99%
“…stand out as aquatic predators of hatchling turtles (Salera Júnior et al, 2009), but other predators may be frogs (Buffo sp. ), caimans (Paleosuchus spp., Caiman crocodilus) and carnivorous fish such as long-whiskered catfish (Pimelodidae), red-tailed catfish (Phractocephalus hemiliopterus), silver arowana (Osteoglossum bicirrhosum), piraiba (Brachyplatystoma filamentosum) and jau (Paulicea luetkeni) (Ibama, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A proibição da caça e comercialização desses animais estabelecidos por lei reduz, mas não elimina o consumo e a venda da P. expansa na região. Estudos sobre o uso ilegal e indiscriminado desse recurso foram apontados no Rio Araguaia (BARROSO e MOURA 2016), no rio Javaés (SALERA JUNIOR et al, 2009;ATAÍDES et al, 2010), em outras localidades da região amazônica como, rio Negro (VOGT, 2001;PEZZUTI et al, 2004,), no Rio Purus (KEMENES e PANTOJA-LIMA, 2006;PEZZUTI et al, 2010) e no Rio Guaporé (FACHÍN-TERÁN e VOGT, 2004).…”
Section: Introductionunclassified
“…A diversidade biológica da região apresenta peculiaridades como, por exemplo, ser a maior planície inundável dentro do bioma o que representa um importante cenário para o desenvolvimento dos quelônios da espécie P. expansa. A presença desses animais na região leva os moradores das http://www.revistas.uneb.br/index.php/ouricuri | ISSN 2317-0131 comunidades tradicionais à prática da caça, comercialização e pesca predatória, o que pode acarretar sérias consequências nos índices populacionais desses animais (SALERA JUNIOR et al, 2009;ATAÍDES et al, 2010).…”
Section: Introductionunclassified